The Influence of Financial Literacy in Digital Learning and Utilization on Students' Entrepreneurial Interest in University - Mutia Seplinda; Harmeli Harmeli; Yonna Anggayu Putri (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to determine the effect of financial literacy in learning and digital utilization on students’ entrepreneurial intention at UPI YPTK Padang. This research used a quantitative approach with a survey method through questionnaires distributed to 50 students. Data analysis used multiple linear regression analysis. The results showed that financial literacy in learning had a positive and significant effect on entrepreneurial intention (t = 3.214; p = 0.003). Digital utilization also had a positive and significant effect on entrepreneurial intention (t = 4.102; p = 0.001). Simultaneously, both variables significantly affected students’ entrepreneurial intention (F = 28.621; p 0.001) with a coefficient of determination (R2) of 0.684, indicating that 68.4% of the variation in entrepreneurial intention could be explained by the proposed model. These findings indicate that financial learning and productive use of digital technology can encourage entrepreneurial intention among university students.